2022
DOI: 10.3390/jcm11206089
|View full text |Cite
|
Sign up to set email alerts
|

Novel Candidate Genes for Non-Syndromic Tooth Agenesis Identified Using Targeted Next-Generation Sequencing

Abstract: Non-syndromic tooth agenesis (ns-TA) is one of the most common dental anomalies characterized by the congenital absence of at least one permanent tooth (excluding third molars). Regarding the essential role of genetic factors in ns-TA aetiology, the present study aimed to identify novel pathogenic variants underlying hypodontia and oligodontia. In a group of 65 ns-TA patients and 127 healthy individuals from the genetically homogenous Polish population, the coding sequences of 423 candidate genes were screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…We summarized and analyzed the genotype–phenotype relationships of NSTA caused by MSX1 variants reported in 1996–2022 (Abid et al., 2017; Adachi et al., 2021; AlFawaz et al., 2015; Arte et al., 2013; Bergendal et al., 2011; Biedziak et al., 2022; Bonczek et al., 2018; Ceyhan et al., 2014; Chishti et al., 2006; Daw et al., 2017; De Muynck et al., 2004; Kamamoto et al., 2011; Keskin et al., 2022; Kim et al., 2006; Kimura et al., 2014; Ma et al., 2020; Mitsui et al., 2016; Mostowska et al., 2006, 2012; Mu et al., 2013; Şahan & Akan, 2021; Tatematsu et al., 2015; Vastardis et al., 1996; Wong et al., 2014; Xin et al., 2018; Xuan et al., 2008; Xue et al., 2016; Yamaguchi et al., 2014; Yang et al., 2020; Yue et al., 2022; Zheng et al., 2021). In brief, we identified 46 patients with 44 MSX1 variants, including the patients in this study (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…We summarized and analyzed the genotype–phenotype relationships of NSTA caused by MSX1 variants reported in 1996–2022 (Abid et al., 2017; Adachi et al., 2021; AlFawaz et al., 2015; Arte et al., 2013; Bergendal et al., 2011; Biedziak et al., 2022; Bonczek et al., 2018; Ceyhan et al., 2014; Chishti et al., 2006; Daw et al., 2017; De Muynck et al., 2004; Kamamoto et al., 2011; Keskin et al., 2022; Kim et al., 2006; Kimura et al., 2014; Ma et al., 2020; Mitsui et al., 2016; Mostowska et al., 2006, 2012; Mu et al., 2013; Şahan & Akan, 2021; Tatematsu et al., 2015; Vastardis et al., 1996; Wong et al., 2014; Xin et al., 2018; Xuan et al., 2008; Xue et al., 2016; Yamaguchi et al., 2014; Yang et al., 2020; Yue et al., 2022; Zheng et al., 2021). In brief, we identified 46 patients with 44 MSX1 variants, including the patients in this study (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…nc/4.0/ -http://creativecommons.org/licenses/by ( EDARADD, KREMEN1, and BMP4. Pathogenic or likely pathogenic nucleotide changes were observed in 56.92% of those affected, including eight nucleotide alterations of genes not previously implicated in non-syndromic tooth agenesis (CHD7, CREBBP, EVC, LEF1, ROR2, TBX22, and TP63) [33].…”
Section: Genetic Causesmentioning
confidence: 95%
“…It was first discovered as a candidate gene in an NSTA individual in 2001 ( Schneider et al, 2001 ) and was first identified in an X-linked inherited NSTA family in 2006 ( Tao et al, 2006 ). To date, 45 mutations in EDA have been linked to NSTA ( Schneider et al, 2001 ; Tao et al, 2006 ; Tarpey et al, 2007 ; Fan et al, 2008 ; Han et al, 2008 ; Li et al, 2008 ; Rasool et al, 2008 ; Mues et al, 2009 ; Song et al, 2009 ; Ayub et al, 2010 ; Mues et al, 2010 ; Arte et al, 2013 ; He et al, 2013 ; Nikopensius et al, 2013 ; Yang et al, 2013 ; Lee et al, 2014 ; Sarkar et al, 2014 ; Zhang et al, 2015 ; Gaczkowska et al, 2016 ; He et al, 2016 ; Shen et al, 2016 ; Bock et al, 2017 ; Martins et al, 2017 ; Yamaguchi et al, 2017 ; Zeng et al, 2017 ; Martínez-Romero et al, 2019 ; Parveen et al, 2019 ; Zhang et al, 2021a ; Biedziak et al, 2022 ; Yu et al, 2022 ), with missense mutations accounting for the majority (39/45). In addition, deletion mutations (3/45), altered splicing (2/45), and non-sense mutation (1/45) were also found in NSTA cases.…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%
“…The EDAR gene is a 425-kb segment located on chromosome 2q11-13. In total, 24 EDAR variants have been identified in NSTA since 2013 ( Arte et al, 2013 ; Chen et al, 2017 ; Yamaguchi et al, 2017 ; Zeng et al, 2017 ; Jonsson et al, 2018 ; Mumtaz et al, 2020 ; Zhang et al, 2020 ; Zhang et al, 2021a ; Zhang et al, 2021b ; Biedziak et al, 2022 ; Yu et al, 2022 ; Zhao et al, 2022 ). As an integral component of the EDA/EDAR/NF-κB signaling pathway, EDAR binds to EDA through the extracellular LBD upstream and interacts with EDARADD through the intracellular death domain downstream.…”
Section: Genetic Basis Of the Eda/edar/nf-κb Signaling Pathwaymentioning
confidence: 99%